Karunungan, Pamana, at Lipunan the former GSIS Building as a student center in Ermita, Manila - Diala, Riel Amadeus A.
The district of Ermita in Manila can be considered as one of the city's educational, political and sociocultural centers. This is supported by the number of established institutions that are located in the district. In fact, one of the city's university belts is located in Ermita, being the location of reputable colleges and schools. The students in the district goes beyond that of such schools, however, considering those from neighboring districts such as Intramuros and Sampaloc visit Ermita for its museums and parks where they may accomplish academic requirements. Arguably, such places lack features to ensure the safety of students in such areas, and said schools themselves are insufficient with necessary facilities to support academic requirements. Manila itself has long been subject to different problems with regards to people's physical and mental health, including environmental pollution and crime. Ermita, as a cultural center, is also the address of different heritage structures -- those that exemplify historical or architectural significance reminiscent of Filipino identity and important for the community. Unfortunately, Manila's built heritage has been a casualty of demolitions executed by those without regard for conservation, perpetuated even by the local government unit responsible for issuing demolition permits in the city. With such problems in mind, this thesis attempts to connect built heritage and education -- two of Ermita's defining aspects -- through the appraisal of existing related facilities, interactions with students and the assessment of existing heritage structures in Manila especially those with uncertain futures due to threats of demolition or dilapidation.